Physiological and microbiological aspects of fresh cut beet roots - Vitti, Maria Carolina Dario; Kluge, Ricardo Alfredo; Gallo, Claudio Rosa; Schiavinato, Marlene Aparecida; Moretti, Celso Luiz; Jacomino, Angelo Pedro (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this work was to evaluate physiological and microbiological aspects of fresh cut beet roots. Respiratory activity and ethylene evolution were evaluated during four hours after processing and during the storage period of ten days at 5°C. Microbiological analysis was carried out right after processing and after ten days of storage. Intact roots showed the lower respiratory activity (5 mL CO2 kg-1 h-1), whereas shredded and peeled beet roots presented a respiration rate of 30 mL CO2 kg-1 h-1 four hours after processing. Fresh cut beet roots showed a peak during the second storage day (80 mL CO2 kg-1 h-1), reducing to 30 mL CO2 kg-1 h-1 at the fourth day. No ethylene evolution was detected in intact and peeled beet roots whereas in the fresh cut material it was observed in the first hours after processing, reaching 0.90 µL kg-1 h-1. Few variations were observed during the four-hour period after processing and during the refrigerated storage. Psychotrophic bacteria and total coliforms counts were within acceptable limits, and no Salmonella or fecal coliforms were detected.